Does gender gap exist in Indian rheumatology? Analysis of faculty gender representation at its annual conferences - Kavitha Mohansundaram; Velu Annamalai Sowndhariya; Vinod Ravindran (Indian Journal of Rheumatology)
Background: Ensuring gender equality in faculty representation at medical academic meetings is important as it is linked to career development, building networks, increasing visibility, and reputation. The objective of this study was to analyze the gender representation among the faculty and abstract presenters at the Indian Rheumatology Association's (IRA) Annual Conferences (IRACONs). Methods: Gender representation among faculty (speakers and chairpersons from India and abroad) and the first author among abstract presenters in the past 10 years (IRACONs 2010–2019) was tabulated. Ratio and proportion of gender representation in these categories were calculated and compared in the two time frames of 2010–2014 and 2015–2019. Trends of female gender representation as faculty and abstract presenters were also compared with trend of enrollment of female life members of the IRA. Results: Female faculty from India constituted 127/627 (20%) and 91/567 (16%) as speakers and chairpersons respectively, with combined representation (speakers and chairpersons) of 18.5% ± 2.34% (mean) over the past 10 years with only few orations (4 out of 29). Widening of gender gap in speaker representation was noted in the latter 5 years' time period of 2015–2019 (23% [3.3:1] vs. 18% [4.6:1]). More females became life members of the IRA in the period 2015–2019, and though a similar positive trend was also noted in female abstract presenters, it was not seen in the female faculty representation. Conclusion: This study confirms that gender gap exists in the representation of female faculty at IRACONs. A systematic approach is required to address this issue by sensitizing the members and developing relevant policies.